1996
DOI: 10.1037/0012-1649.32.2.195
|View full text |Cite
|
Sign up to set email alerts
|

The relations of children's dispositional empathy-related responding to their emotionality, regulation, and social functioning.

Abstract: The relations of kindergartners' to 2nd graders' dispositional sympathy to individual differences in emotionality, regulation, and social functioning were examined. Sympathy was assessed with teacher-and self-reports; contemporaneously and 2 years earlier, parents and teachers reported on children's emotionality, regulation, and social functioning. Social functioning also was assessed with peer evaluations and children's enacted puppet behavior, and negative arousability-personal distress was assessed with phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
294
0
17

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(327 citation statements)
references
References 64 publications
(110 reference statements)
11
294
0
17
Order By: Relevance
“…Moreover, approximately half of the sample had children who were displaying clinical levels of externalizing and/or internalizing problem behaviors. Given previous work linking problem behaviors and negative emotionality (Eisenberg, Fabes, Murphy, Karbon, et al, 1996), it is possible that effortful control plays a more important function in this sample than in less clinical samples. Therefore, before replicated in more representative samples, caution should be exercised when generalizing these findings.…”
Section: Limitations Of the Studymentioning
confidence: 98%
“…Moreover, approximately half of the sample had children who were displaying clinical levels of externalizing and/or internalizing problem behaviors. Given previous work linking problem behaviors and negative emotionality (Eisenberg, Fabes, Murphy, Karbon, et al, 1996), it is possible that effortful control plays a more important function in this sample than in less clinical samples. Therefore, before replicated in more representative samples, caution should be exercised when generalizing these findings.…”
Section: Limitations Of the Studymentioning
confidence: 98%
“…In fact, we are aware of no findings linking deficient autonomic responding to deficits in empathy observed during emotion induction using films. In studies where empathy has been linked with autonomic responding among children, the relation has usually been correlational and indirect (e.g., boys with DBDs have generalized low autonomic arousal and exhibit limited empathy; Eisenberg et al, 1996). Moreover, although Liew et al (2003) did measure skin conductance and heart rate, linking lower reactivity in each to less empathy, this study (a) was conducted with a normative sample and (b) linked ratings of empathy to autonomic reactivity to static facial expressions of emotion (slides).…”
Section: Discussionmentioning
confidence: 99%
“…First, the construct of effortful control is broader than that of anger-control, encouraging a more extensive conceptualization of agreeableness as self-regulation. As such, agreeableness may be associated with the selfregulation of forms of negative emotionality other than anger, including anxiety and depression (Eisenberg et al, 1996).…”
Section: Agreeableness As Effortful Controlmentioning
confidence: 99%
“…First, the construct of effortful control is broader than that of anger-control, encouraging a more extensive conceptualization of agreeableness as self-regulation. As such, agreeableness may be associated with the selfregulation of forms of negative emotionality other than anger, including anxiety and depression (Eisenberg et al, 1996).Second, it has been suggested that effortful control is particularly important among children with temperamental tendencies toward negative affect, presumably a precursor of neuroticism (Ahadi & Rothbart, 1994;Eisenberg, Fabes, Guthrie, & Reiser, 2000;Nigg, 2006). In the developmental literature, a frequent finding is that, among children high in negative emotionality, those high in effortful control are less vulnerable to mood-disordered outcomes (e.g., Eisenberg et al, 2000; see Nigg, 2006).…”
mentioning
confidence: 99%